A Religio-philosophical appraisal of moral evil in relation to banditry in Nigeria - Oyebanji , Israel Temitope; Fashola, Joseph Omokafe; Adekoya, Samuel Olamide; Ogunbiyi, David Oluwabukunmi (Corpus Intellectual, 2024)
One of the most lasting and vigorous issues Nigerians have ever faced is the threat to life, which is a product of a persistent phenomenon called insecurity. The problem of insecurity has therefore taken diverse forms, especially in the north-eastern part of Nigeria banditry is very rampant. Much research work has been done on the concept of banditry in Nigeria, however, little or no attention has been paid to the banditry from a philosophical perspective. It is on this ground that the researcher intends to examine the notion of moral evil in relation to banditry in Nigeria. A combination of philosophical and phenomenological approaches was used in examining available texts, which constitute the work’s primary sources of data collection for this research, wherein Books, articles, journals, and online resources that are relevant to the research were consulted. The results showed that banditry is a moral evil that should be excluded from the domain of God since it is caused by man’s actions and inaction in the environment. The result also shows that the prominent cause of banditry in Nigeria is a result of failed government policies and corruption. The study concluded that the loss of lives and properties as a result of banditry is purely a product of man’s action and inaction in his environment. The study recommends that the Nigerian government should rise to the occasion of taming and ending banditry in the country.